Analisis Perbandingan File Sharing Pada Sistem Terdistribusi Berbasis Cloud - Uswatul Hasana; Massikki Massikki; Isna Aulia Azzahra (Journal of Renewable Energy and Smart Device, 2025)
This study examines the performance and features comparison of three cloud-based file sharing services Google Drive, Dropbox, and OneDrive within the context of distributed systems. The primary objective is to analyze upload and download speed, security features, collaboration ease, and free storage capacity of each platform. A comparative method with direct experimentation was employed, where files sized 10 MB, 50 MB, and 100 MB were tested on each platform to obtain average transfer times. The results indicate that Dropbox excels in data transfer speed, Google Drive offers larger free storage and superior real-time collaboration features, while OneDrive stands out for its integration with Microsoft Office applications. All three services demonstrate high levels of data security and availability due to the implementation of distributed systems supporting data encryption, replication, and load balancing. This study provides insights for users to choose a storage platform that suits their needs and encourages further development of more efficient and secure cloud systems.